The Sociological Study of Emotions: Interactionist Analysis Lines - Cerulo, Massimo (Italian Sociological Review, 2019)
The main goal of this article is to trace some guidelines for a sociological study of emotions. By using the scientific approach of the Symbolic Interactionism, the main features of the interactionist study of emotions will be presented focusing on the processes that characterize the emotional experience of the daily life: naming, experience and construction of the emotional reality. In this context, we will go through the ‘four-factor model of emotion’ as well as the process related to the emotional socialization.